BANK1 functional variants are associated with susceptibility to diffuse systemic sclerosis in Caucasians. Issue 4 (8th October 2009) - Rueda, B; Gourh, P; Broen, J; Agarwal, S K; Simeon, C; Ortego-Centeno, N; Vonk, M C; Coenen, M; Riemekasten, G; Hunzelmann, N; Hesselstrand, R; Tan, F K; et al.
Abstract : Objective: To investigate the possible association of the BANK1 gene with genetic susceptibility to systemic sclerosis (SSc) and its subphenotypes. Methods: A large multicentre case–control association study including 2380 patients with SSc and 3270 healthy controls from six independent case–control sets of Caucasian ancestry (American, Spanish, Dutch, German, Swedish and Italian) was conducted. Three putative functional BANK1 polymorphisms (rs17266594 T/C, rs10516487 G/A, rs3733197 G/A) were selected as genetic markers and genotyped by Taqman 5´ allelic discrimination assay. Results: A significant association of the rs10516487 G and rs17266594 T alleles with SSc susceptibility was observed (pooled OR=1.12, 95% CI 1.03 to 1.22; p=0.01 and pooled OR=1.14, 95% CI 1.05 to 1.25; p=0.003, respectively), whereas the rs3733197 genetic variant showed no statistically significant deviation. Stratification for cutaneous SSc phenotype showed that the BANK1 rs10516487 G, rs17266594 T and rs3733197 G alleles were strongly associated with susceptibility to diffuse SSc (dcSSc) (pooled OR=1.20, 95% CI 1.05 to 1.37, p=0.005; pooled OR=1.23, 95% CI 1.08 to 1.41, p=0.001; pooled OR=1.15, 95% CI 1.02 to 1.31, p=0.02, respectively). Similarly, stratification for specific SSc autoantibodies showed that the association of BANK1 rs10516487, rs17266594 and rs3733197 polymorphisms was restricted to the subgroup of patients carrying anti-topoisomerase I antibodies (pooled OR=1.20, 95% CI 1.02 to 1.41, p=0.03; pooled OR=1.24, 95% CI 1.05 to 1.46, p=0.01; pooled OR=1.26, 95% CI 1.07 to 1.47, p=0.004, respectively). Conclusion: The results suggest that the BANK1 gene confers susceptibility to SSc in general, and specifically to the dcSSc and anti-topoisomerase I antibody subsets.